Digital Tax Literature Mapping: A Top Bibliometric Analysis Global Publications 2010–2023 - Puspitasari, Novia; Haryanto, Haryanto (Jurnal Akuntansi dan Perpajakan, 2025)
In this increasingly advanced era, digital transformation has triggered fundamental changes in the global tax system, including in Indonesia, which is now faced with the challenges of supervision, compliance, and fiscal justice in an economic ecosystem without physical borders. This study aims to conduct a bibliometric analysis of the scientific literature on digital taxes in Indonesia, focusing on publication trends, main themes, and mapping the direction of future research. Using the PRISMA approach and data from Scopus during the period 2010–2023, a total of 496 English-language articles were analyzed using RStudio and Biblioshiny devices. The results show a significant trend of publication growth with an average annual increase of 30.66%, as well as the dominance of topics such as digital storage, taxation, and fiscal policy. The findings also show that there is still limited exploration of data privacy, sustainability, and social perspectives in digital taxation studies. Therefore, this study underlines the importance of increasing the contribution of interdisciplinary and contextual national research as the basis for the formulation of responsive and inclusive digital fiscal policies in Indonesia.